2018
DOI: 10.1055/s-0038-1670663
|View full text |Cite
|
Sign up to set email alerts
|

Complex Valve Surgery in Elderly Patients: Increasingly Necessary and Surprisingly Feasible

Abstract: This study demonstrates the feasibility of complex multiple valve surgery in elderly patients. The observed perioperative mortality was lower than predicted. However, we observed a substantial rate of adverse events; therefore, careful patient selection is required in this high-risk patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Immunosenescence and multiple comorbidities render older patients susceptible to IE [15,16]. Furthermore, major factors that determine postoperative outcome are the disease-independent influence of the biological aging process and, therefore, the cellular and tissue aging process, in addition to the presence of comorbidities such as advanced atherosclerosis, impaired diastolic heart function, renal insufficiency, reduced lung compliance, and respiratory muscle strength [17,18]. Nutritional and functional status have also been found to be independent predictors of mortality in older patients suffering from IE [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosenescence and multiple comorbidities render older patients susceptible to IE [15,16]. Furthermore, major factors that determine postoperative outcome are the disease-independent influence of the biological aging process and, therefore, the cellular and tissue aging process, in addition to the presence of comorbidities such as advanced atherosclerosis, impaired diastolic heart function, renal insufficiency, reduced lung compliance, and respiratory muscle strength [17,18]. Nutritional and functional status have also been found to be independent predictors of mortality in older patients suffering from IE [15].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional and functional status have also been found to be independent predictors of mortality in older patients suffering from IE [15]. Complex valve surgery, even in the setting of reoperation in older patients, has been reported to be feasible with good outcomes [18,19]. Although cardiac surgery in elderly patients has been reported to be associated with an improvement in HRQOL, a decline in HRQOL has been reported in about 8-19% of patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, patients suffering from TIE were significantly older than those suffering from SAVR–PVE, and this is not surprising. Although advanced age is associated with higher risk of death, longer hospital stay, and neurologic complications, it is dependent on the patients’ comorbidities, level of dependence, and nutritional and cognitive status; therefore, age itself should not be a contraindication to complex valve surgery [ 24 , 25 ]. Furthermore, we found that a significantly higher proportion of the patients in the TIE-group were immunosuppressed on chronic steroid therapy, which has been identified as a risk factor for TIE [ 20 ].…”
Section: Commentmentioning
confidence: 99%
“…This trend is also reflected in the surgical population, where the care for older persons (although often challenging) has become quite common [ 5 ]. Old age is related with a decline in physiological reserve [ 6 , 7 ] and most of these patients will present themselves with more risk factors than their younger counterparts [ 8 ]. Although advantages in prehabilitation, operative techniques and perioperative management seem to improve outcome and quality of life in octogenarians, postoperative adverse events remain more common in elderly patients.…”
Section: Introductionmentioning
confidence: 99%